A colorimetric and ratiometric fluorescent probe with a large stokes shift for detection of hydrogen sulfide. (December 2015) - Xiang, Kaiqiang; Liu, Yunchang; Li, Changjiang; Tian, Baozhu; Tong, Tianzhong; Zhang, Jinlong
Abstract: Developing probes for selective and sensitive detection of hydrogen sulfide (H2 S) has received much research attention, because H2 S is an environmental toxin as well as an important signaling molecule to regulate physiological and pathological processes. In this work, a new colorimetric and ratiometric fluorescent probe (Probe 1) for H2 S detection was synthesized by employing dicyanoisophorone based fluorescence dye as a fluorophore and azide group as the response unit. The synthesized Probe 1 showed a long emission wavelength ( λ em = 643 nm) and large stokes shift ( λ em − λ abs = 163 nm). Based on the H2 S-induced reduction of azide group to amino group, Probe 1 showed high response speed, sensitivity, and selectivity toward HS − under room temperature. Moreover, Probe 1 can ratiometrically respond to HS − and the detection limit is as low as 0.13 μM. It was proved that Probe 1 is suitable for quantitatively detecting HS − ions in river water samples. The numerous advantages of Probe 1 make it be potentially used for quantitative detection of H2 S in environment and living organisms. Graphical abstract: Highlights: A ratiometric fluorescence probe for H2 S was synthesized using dicyanoisophorone as fluorophore. The probe showed long emission wavelength (643 nm) and large stokes shift (163 nm). The probe exhibited high response speed and selectivity toward H2 S. The probe showed high sensitivity toward HS − and the detection limit is as low as 0.13 μM.